Long Spine Mooring - Retzler, Chris-Heinz (The University of Edinburgh, 1986)
In this report we present the specification of the mooring for the long spine model, and a detailed analysis of its static and dynamic characteristics. We describe the experimental investigations of the behaviour of the mooring alone, and coupled to the spine, in a variety of multidirectional seas representative of the full range of North Atlantic conditions. In preliminary experiments some seas caused the spine to sway axially. Adoption of a new mooring plan solved the problem completely.